The paradox of state identification: de facto states, recognition, and the (re-)production of the international. Issue 3 (November 2019) - Grzybowski, Janis
Abstract: The literature on de facto states challenges the conventional identification of states by legal recognition, proposing to identify states based on their effectiveness instead. Yet, as I argue in this paper, rather than turning the tables on recognition, the de facto state challenge ultimately reveals all state identification in International Relations and international law to be essentially indeterminate. This lacuna, I suggest, is not an accidental omission, but an expression of the foundational paradox of modern political order that is rooted in the intertwined ontology of the state system and the individual states constituting it, with each presupposing the other. As a result, the opposition between empirical facts, political decisions, and legal norms invoked in attempts to identify states cannot but remain irresolvable. This should not be regarded as a problem to be overcome, however, but as a source of social order. Although states cannot be substantively identified, any effort to do so in practice naturalizes the state as the very form through which we articulate and shape political claims, conflicts, and settlements. In performatively enacting states precisely at the contested margins, state identification thus both invokes and (re-)produces the statist international as the central imaginary of modern political order.